In the deeper recesses of a case of narcissistic violence, could one listen for a missing symbiotic link to anOther for a Subject to come to be?: case of J. - Tiwari, Priya (Psychoanalytic Psychotherapy, 2025)
The paper follows a psychotherapy journey with J., an adolescent who perpetrated an irreversible act of violence on a peer. The paper charts through shifts in the therapeutic field with J., a transformation from this state into an emerging sense of a Subject in J. There was a moment of humiliation provoking the act of violence, which might be seen as an act of narcissistic violence. The focus in the paper is on the factors that may have allowed for transformation in this self experience. Indicating a deeper story of shame that betrays the unconscious need for a symbiotic link with some depositories in life. The paper also makes some links to the role of Justice itself as a depository of this level of dependence that has been noted by many object relations thinkers in noting an ineffable subject of the unconscious, skin as creating an intersensorial floor, in foregrounding 'soma' and intercorporeality. The author elaborates on the role and significance of the field of relating at a primitive level of dependence that may need to be supported and tolerated even if ambiguously, at first, to come to be subjectivised into an emerging sense of a Subject that can speak.